Generalists and specialists: Two sides of the same coin for cancer care?: Amid growing concern over a decline in generalists, experts are urging new incentives to extend their reach and are paying more attention to key generalist tools that even specialists can tap. Issue 2 (2nd February 2023) - Nelson, Bryn; Faquin, William
Abstract : This news section is written by a medical journalist and offers Cancer Cytopathology readers timely information on events, issues, and personalities of interest to the subspecialty. In this issue, a decline in generalists has specialists extending their reach and paying more attention to key generalist tools that they can tap.